Nonlinear hrv indices in response to an incremental test in young cyclists - Camarena, B.; Blasco-Lafarga, C.; Mateo, M.; Montoya, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Volume is a key factor in cycling sports, what may trigger negative effects, increasing the importance of individualizing workloads, mainly in younger cyclist. Ventilatory thresholds become, thus, of paramount importance. Recent studies suggest that some nonlinear indices of Heart Rate Variability (HRV) are sensible to the specific changes in the neural cardiac modulation at different intensities (1), providing objective and non-invasive information on the Anaerobic Threshold (AT) (2-4). This study aims to analyze HR dynamics in a graded test in trained cadets, looking for relationships between HRV indices and ventilatory cut-points, since little is known about HRV changes in younger cyclist and its application in determining AT. Methods: 14 male national-level road cyclists (15±0.5 y) underwent a cycle-ergometer graded-test (increments of 30 W every 4:30 sec; from 60% to 100% in a previous test), ending at voluntary exhaustion, or when cyclists were unable to maintain the required cadence. RR intervals were recorded along the test, retaining the last 3 min of every stage for further analysis (Kubios HRV 2.0). A one way repeated measures ANOVA, controlling for the weight, was employed to elucidate the effect of fatigue on RRi, and the nonlinear SD1, DFA1 and SampEn. Bonferroni post-hoc was applied when necessary. Correlation analysis between conventional performance parameters RQ, [La] and RPE, and nonlinear indices were also considered at 100%. Results: DFA1 decreased largely along the test (DFA100%: 0.29+0.13). Regarding Fatigue, Bonferroni showed changes at 80% for DFA1 (p=0.003; 0.45±0.14) and RQ (p=0.049; 0,96±0,03). Significant negative correlations were found between DFA1 and RPE (p<0.05; r=-0.7) and VO2/kgmin (p<0.05; r=-0.8), while RPE and SampEn correlated positively (p<0.05; r=0.7). Discussion: Compare to adults (3), SD1 has no reflected the AT, whilst DFA1 and SampEn have changed significantly at 80%, with lactate around 4 mmol. Further studies should analyze differences in the nonlinear HRV indices regarding the age at the AT.